Review of Islamic Criminal Law on the Crime of Rape - Aniksya Nabila Safikoh; Yusuf Harahap (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
This article aims to comprehensively discuss and assess the crime of rape within the context of Indonesian criminal law. The crime of rape is regulated under Article 285 of the Indonesian Criminal Code, which encompasses various elements that must be met, one of which is the element of violence. This element of violence is the main distinguishing factor between rape and other moral violations regulated in the Criminal Code. In the justice system, law enforcement officers impose appropriate penalties on perpetrators of sexual violence to uphold the rule of law, maintain social order, and provide a deterrent effect so that perpetrators do not repeat their actions, while also serving as a deterrent so that others do not commit similar acts.